2012
DOI: 10.1016/j.snb.2012.04.062
|View full text |Cite
|
Sign up to set email alerts
|

Stable optical oxygen sensing materials based on click-coupling of fluorinated platinum(II) and palladium(II) porphyrins—A convenient way to eliminate dye migration and leaching

Abstract: Nucleophilic substitution of the labile para-fluorine atoms of 2,3,4,5,6-pentafluorophenyl groups enables a click-based covalent linkage of an oxygen indicator (platinum(II) or palladium(II) 5,10,15,20-meso-tetrakis-(2,3,4,5,6-pentafluorophenyl)-porphyrin) to the sensor matrix. Copolymers of styrene and pentafluorostyrene are chosen as polymeric materials. Depending on the reaction conditions either soluble sensor materials or cross-linked microparticles are obtained. Additionally, we prepared Ormosil-based se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
52
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 49 publications
2
52
0
2
Order By: Relevance
“…More hydrophilic carriers might require adaptation of the labeling procedure, using covalent fixation or other forms of deposition of the luminophore(s) on the surface, for example. However, manufacture of optical chemical sensors has been confronted with similar challenges, and there are already useful solutions to overcome them [187,211]. Hydrogels applied for encapsulation of enzymes and cells should be generally amenable to the fluorescence labeling [186].…”
Section: Expanding To Other Analytes and Biocatalystsmentioning
confidence: 99%
“…More hydrophilic carriers might require adaptation of the labeling procedure, using covalent fixation or other forms of deposition of the luminophore(s) on the surface, for example. However, manufacture of optical chemical sensors has been confronted with similar challenges, and there are already useful solutions to overcome them [187,211]. Hydrogels applied for encapsulation of enzymes and cells should be generally amenable to the fluorescence labeling [186].…”
Section: Expanding To Other Analytes and Biocatalystsmentioning
confidence: 99%
“…PtTFPP was also modified to be able to be polymerized and cross-linked with hydrophilic poly(2-hydroxyethyl methacrylate)-co-polyacrylamide or hydrophobic polystyrene to generate highly photostable and biocompatible sensing films [216]. Nucleophilic substitution of the parafluorine atoms of the pentafuorophenyl groups allows covalent coupling to polymeric materials such as polystyrene copolymers [114] and silica gel [25]. Due to its excellent photostability, PtTFPP has been extensively used for those applications in which high light intensities are used, primary in fiber-optic microsensors and microscopy [69], but also in multi-analyte sensors and as components for pressuresensitive paints [76].…”
Section: Metalloporphyrinsmentioning
confidence: 99%
“…The metalloporphyrin PtOEP and the free porphyrin base H 2 OEP (OEP = 2,3,7,8,12,13,17,18-octaethyl-21H,23H-porphine) were selected because of their wide-ranging applications. [10][11][12] DFT calculations showed that the molecular electrostatic potentials (MEPs) of H 2 OEP and PtOEP exhibit an electronrich (p-basic) region at the center of the squares whereas [Ag 3 (m 1,2 -3,5-(n-C 3 F 7 ) 2 Tz) 3 ] (1) is very electron-poor (strongly p-acidic) at the center of the nine-membered ring (Scheme 1 b Figure 1) with one benzene molecule per asymmetric unit. The adduct pair consists of fluorous bowl-shaped 1 and H 2 OEP, which are held together by coordination, p-stacking (quadrupole-quadrupole), and van der Waals forces.…”
mentioning
confidence: 99%